The Correlation Between Lecturers’ Communication Style and English Students’ Motivation in Thesis Writing: (A Correlation Study at Semester VIII of the Department of English Language Education at Universitas Hasyim Asy’ari) - Putri Tiara Zahrotul Mukaromah; Sayid Marifatulloh (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to investigate students’ perceptions of lecturers’ communication styles and to examine the correlation between lecturers’ communication style and students’ motivation in thesis writing. This research employed a quantitative approach with a correlational design involving students of the Department of English Language Education at Hasyim Asy’ari University who were in the process of completing their thesis. Data were collected through a questionnaire measuring two variables, namely lecturers’ communication style and students’ motivation, and were analyzed using descriptive statistics and Pearson product-moment correlation with the help of SPSS. The findings revealed that students generally have positive perceptions of lecturers’ communication styles during thesis supervision, as indicated by the high mean score of the communication variable. Furthermore, the results of the correlation analysis showed a very strong and significant positive relationship between lecturers’ communication style and students’ motivation in thesis writing, indicating that better communication from lecturers is associated with higher levels of student motivation. These findings emphasize the importance of effective, clear, and supportive communication in enhancing students’ motivation and facilitating the thesis completion process. Therefore, lecturers are encouraged to adopt communicative and collaborative approaches to create a more engaging and motivating academic environment. This study contributes to the existing literature by providing empirical evidence in the context of thesis supervision, which has received limited attention in previous research.